Sexual Orientation and Gender Identities: An Analysis of the Contemporary Laws and Literature - Yonzon, Dhruba (Kathmandu School of Law Review, 2018)
Where the expression of sexual orientation and gender identities is one of the fundamental human rights of an individual, there many people still face threat to their liberty and to their lives. Culture and religion play a vital role in establishing such detrimental ideologies; where, despite the understanding that every human being is born equal in freedom and in dignity, millions of queer people are deprived of their right, therefore being discriminated and at worst being persecuted with a simple reasoning that homosexuality is “unnatural” and is a “sin”. This paper will analyze the response of several nations in the Universal Periodic Review regarding their discriminatory law against the LGBT+ (it denotes – Lesbian, Gay, Bisexual, Transgender including other member of the queer community, hereafter "LGBT+") individual. Further, the paper will establish how media and literature have misled to the general public reinforcing ideas that being anything other than “straight” or “cis-gendered” is not “normal” and could be never, which allows States to opt for these inhumane treatments against the LBGT+ people without any recourse. At the end, the paper puts forth approaches to properly implement international human rights law in protection of LGBT+ individuals in law and in daily life.